PENGARUH HUMAN CAPITAL TERHADAP KUALITAS AUDITOR PADA KANTOR AKUNTAN PUBLIK DI SEMARANG - Oneal Savitri; Herry Laksito (Diponegoro Journal of Accounting, 2013)
The purpose of this research is to examine the influence of human capital toward auditor’s quality in Public Accounting Firm at Semarang. The auditor quality which is the dependent variable will influence human capital as independent variablel. Human capital is consisted of formal education level, working experience, professional qualification level of auditor and continuing professional development. The population in this research are auditor in Public Accounting Firm at Semarang, Indonesia The result are all independent variable that is human capital simultantly have positif influence for auditor quality. The analysis for independent variable partially, only formal education level, working experience, and CPD that have a significant influence of the auditor quality Professional qualification level have not significant influence with auditor